Has the Incidence of Inflammatory Bowel Disease Peaked? Evidence From the Population-Based NorDIBD Cohort 1978–2020. (13th March 2023) - Larsen, Lone; Karachalia Sandri, Anastasia; Fallingborg, Jan; Jacobsen, Bent Ascanius; Jacobsen, Henrik Albæk; Bøgsted, Martin; Drewes, Asbjørn Mohr; Jess, Tine
Abstract : INTRODUCTION: While the incidence of inflammatory bowel disease (IBD) is rising globally, it has been suggested to stabilize in westernized countries, but this has not yet been shown in exhaustive and large cohorts. We generated an IBD cohort in North Denmark (NorDIBD) of 6, 158 patients with IBD diagnosed from 1978 to 2020, based on all recorded and verified IBD diagnoses in the region. While describing the establishment of this cohort, we aimed to present the accurate incidence and prevalence of IBD over 4 decades. METHODS: The NorDIBD cohort covered all pediatric and adult patients with an IBD diagnosis dated between January 1, 1978, and December 31, 2020, and living in North Denmark, hence forming an unselected population-based patient cohort. IBD incidence rates between 1978 and 2020 and IBD point prevalences between 2003 and 2020 were calculated. RESULTS: We observed a 4-fold increase in the incidence of IBD from 11.5 per 100, 000 persons (95% confidence interval [CI] 8.4–14.6) in the year 1978 to 51.3/100, 000 (95% CI 45.5–57.1) in the year 2014, whereas in 2020, this rate stabilized. The overall prevalence of IBD more than doubled from 2003 to 2020, from 424 (95% CI 407–443) in 2003 to 872 (95% CI 849–896) IBD cases per 100, 000 persons in 2020. DISCUSSION: Our population-based NorDIBD cohort suggests stabilizing of the incidence of IBD in Denmark, whereas the prevalence continues to rise. Because the data represent a 10% sample of the entire Danish IBD population, we believe that data can be extrapolated to the IBD population in general and used for healthcare planning. Abstract :